2022
DOI: 10.1037/cou0000616
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking leader responsiveness effects of emotional cultivation groups: Using the variance partitioning method.

Abstract: Theoretically, group leaders can play a significant role in contributing to the effectiveness of group counseling intervention. However, very few studies have examined the group leader's effects on the clientrated group counseling outcomes. We hypothesized that responsive group leaders who were caring, understanding, and respectful could serve as safe havens and secure bases to facilitate their group members' social and emotional cultivation. The current investigation examined the effects of leader responsiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Theoretically, it is also important to examine within-group differences and between-group differences in predictors, like group climate. For example, Wang et al (2022) showed that greater member-perceived leader responsiveness and greater group-as-a-whole-perceived leader responsiveness were both related to member improvement. The variance partitioning of predictor variables needs to be done manually in multilevel models as described by Kivlighan and Kivlighan (2016).…”
Section: Group Member (Within-group) and Group-as-a-whole (Between-gr...mentioning
confidence: 99%
“…Theoretically, it is also important to examine within-group differences and between-group differences in predictors, like group climate. For example, Wang et al (2022) showed that greater member-perceived leader responsiveness and greater group-as-a-whole-perceived leader responsiveness were both related to member improvement. The variance partitioning of predictor variables needs to be done manually in multilevel models as described by Kivlighan and Kivlighan (2016).…”
Section: Group Member (Within-group) and Group-as-a-whole (Between-gr...mentioning
confidence: 99%